2018
DOI: 10.7759/cureus.2432
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin Augmentation of Levetiracetam Treatment: A Case of Forced Normalization With Emergence of Psychosis

Abstract: Forced normalization is the emergence of psychoses following stabilization of seizures in an uncontrolled epileptic patient. The current study is a case of forced normalization, a phenomenon characterized by normalization of electroencephalogram (EEG) findings and resolution of seizures. This case report is unique and rare because the patient meets the diagnostic merit of forced normalization, which occurred due to a nonconventional method of seizure control management. We discuss the recognition and different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…There is a clear predominance of patients with developmental delay (60 %) while Calle-López reported 24.2 % of patients with forced normalization with developmental delay [11]. In previous reports, some patients had Lennox-Gastaut syndrome or congenital encephalopathy [23][24][25], but in other cases the absence of developmental delay/ absence of neurologic comorbidity is clearly stated [26][27][28][29][30][31]. Some other cases do not report the previous neurological status, being therefore unknown [19,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…There is a clear predominance of patients with developmental delay (60 %) while Calle-López reported 24.2 % of patients with forced normalization with developmental delay [11]. In previous reports, some patients had Lennox-Gastaut syndrome or congenital encephalopathy [23][24][25], but in other cases the absence of developmental delay/ absence of neurologic comorbidity is clearly stated [26][27][28][29][30][31]. Some other cases do not report the previous neurological status, being therefore unknown [19,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…There were also reports of FN caused by valproic acid (VPA), phenytoin (PHT), and zonisamide (ZNS)[ 4 , 5 , 9 ]. In recent years, studies on the relationships between FN and ASMs have focused more on levetiracetam (LEV)[ 11 , 12 ]. In 2018, Esang et al [ 12 ] systematically discussed the clinical features and treatment strategies for FN and explored its relationship with ASMs, which made the clinical diagnosis and treatment of FN more rational.…”
Section: Historical Evolution Of Fnmentioning
confidence: 99%
“…Based on the patient's clinical course, this author believes that she developed FN by taking PHT. Esang et al [ 12 ] reported a 26-year-old female patient with no history of mental illness. Her family members described that she had been diagnosed with epilepsy in 2016 and received LEV treatment, which was initially effective; however, she had frequent seizures 1 year later, and then PHT (0.1 g tid) was added.…”
Section: Clinical Features Of Fnmentioning
confidence: 99%